Estrategia didáctica para el aprendizaje del principio de pascal en estudiantes de tercer año de bachillerato general unificado de la Unidad Educativa “Ángel Polibio Chaves”, del cantón Guaranda, provincia Bolívar, durante el período lectivo (noviembre 2022 – marzo 2023) - Rodríguez Arellano, Brayan Stiben (2023)
In the subject of physics there are several very important topics and one of them is Pascal's Principle, which is found within the study of the hydraulic branch and in such a way, it is necessary to know what it consists of, what are its applications and how this is applied. is reflected in the action of daily living. The characteristic of fluids due to liquids was based on the pressure that exists in them, therefore, it is necessary that forces are exerted on different surfaces, since said force is a unit of pressure on a specific area. The physical-mathematical philosopher Blaise Pascal observed that when the pressure applied to a surface is increased, this same pressure increases by the same amount, which when exerting a pressure on a fluid, will unfold in an equal magnitude towards all directions at each part of the fluids, this is called Pascal's principle. Therefore, Pascal also determined that there are two types of fluids according to their behavior when they are subjected to pressure: Compressible fluids.- This type of fluid can expand or compress depending on the pressure exerted on them, for example: gases are the type of comprehensible fluids. Incompressible fluids.- This type of fluid cannot change its volume either due to pressure effects, for example: liquids and solids are the type of incompressible fluids. Pascal's principle is always evident in a hydraulic press and it is made up of two containers with rigid walls, each of these walls contains incompressible fluids and both containers are internally connected, thus in each of the containers the height of the fluids is the same, except that the peculiarity of this system is that each cross-sectional area that each container contains is different, since one of them is less than the proportion of the other.